From tweet to tremor: Enhancing megathrust disaster monitoring and early warning systems in social media - Silvia Nur Aulia Elsa; Saepudin Epin; Qoriah; Ernawati; Khoiri Shohib; Kusumawati Azhari Siti (E3S Web of Conferences)
This researches how to explores the potential of social media in improving megathrust disaster monitoring and early warning systems, focusing on two regions in Indonesia: Gunung Kidul and Tanggamus. Using a quantitative approach through a questionnaire-based survey, the research reveals that most respondents (70% in Gunung Kidul and 85% in Tanggamus) consider the internet/social media as an important source of information during disasters. Furthermore, 70% of respondents in Gunung Kidul and 85% in Tanggamus are willing to receive official warnings through these platforms. Nonetheless, challenges related to data verification and reliability of information on social media still exist. Only 12% of respondents in Gunung Kidul and 8% in Tanggamus considered social media to be very reliable as a source of disaster information. This finding underscores the importance of collaboration between the government, disaster management agencies and social media platforms to ensure the accuracy of information disseminated. Overall, this study provides empirical evidence on the potential of utilizing social media to improve early warning systems and response to megathrust disasters. The integration of social media into disaster mitigation strategies can provide significant benefits, especially in terms of early detection, enhancing situational awareness, and facilitating communication and collaboration during disasters.